Hubungan Lama Penggunaan Ortodonti Cekat dengan Status Psikososial - Puspitasari, Yustisia; Novawaty, Eva; Abdi, Muhammad J.; Alifjayani, Syahfira (e-GiGi, 2026)
Abstract: Orthodontic treatment aims to improve orofacial aesthetics and function, by moving teeth or modifying jaw growth. Psychosocial describes the interaction between behavior, social influences, environment on the mind, and culture. This study aimed to analyze the relationship between duration of fixed orthodontics use and psychosocial status. This was an observational and analytical study with a cross-sectional design. Data were analyzed using the chi-square test. Samples were patients using fixed orthodontics at Kimia Farma Cendrawasih Clinic. The results showed that 40 patients were included in this study as respondents. The highest percentage of respondents was those who had used fixed orthodontics for >2 years (42.5%), followed by less than one year (32.5%), and 1-2 years (25.0%). Related to psychosocial status, most respondents had moderate psychosocial status (50%), followed by good psychosocial status (35.0%), and poor psychosocial status (15.0%). The chi-square test obtained a p-value of 0.021 for the relationship between the duration of using orthodontics and psychosocial status. In conclusion, there is a significant relationship between duration of fixed orthodontics use and psychosocial status among the patients. Keywords: duration of use; fixed orthodontics; psychosocial status   Abstrak: Perawatan ortodonti bertujuan untuk memperbaiki estetika dan fungsi orofasial, dengan cara menggerakkan gigi atau memodifikasi pertumbuhan rahang. Psikososial merupakan gambaran interaksi antara perilaku, pengaruh sosial, lingkungan pada pikiran, dan budaya. Penelitian ini bertuju untuk mengetahui hubungan lama penggunaan ortodonti cekat dengan status psikososial. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Uji statistik yang digunakan ialah uji chi-square. Sampel penelitian ini ialah pasien Klinik Kimia Farma Cendrawasih yang melakukan perawatan ortodonti di dokter Spesialis Ortodonti. Hasil penelitian mendapatkan 40 pasien sebagai responden. Responden terbanyak ialah responden yang memiliki lama penggunaan ortodonti cekat >2 tahun (42,5%), diikuti lama penggunaan <1 tahun (32,5%), dan lama penggunaan 1-2 tahun (25,0%). Terkait status psikososial, responden terbanyak memiliki status psikososial sedang (50%), diikuti status psikososial baik (35,0%), dan status psikososial buruk (15,0%). Hasil uji chi-square terhadap hubungan antara lama penggunaan ortodonti cekat dengan status psikososial mendapatkan nilai p=0,021. Simpulan penelitian ini ialah terdapat hubungan bermakna antara lama penggunaan ortodonti cekat dengan status psikososial pasien. Kata kunci: lama penggunaan; ortodonti cekat; status psikososial